THE INFLUENCE OF DEEP LEARNING ON STUDENTS’ CRITICAL AND HISTORICAL THINKING SKILLS - Fatimah Juliana Hasibuan hasibuan (NAPAK TILAS: Jurnal Pendidikan Sejarah dan Ilmu Sejarah, 2025)
This article examines the influence of deep learning–oriented instruction on students’ critical and historical thinking skills in history education. Deep learning emphasizes meaningful understanding, active inquiry, reflection, and the integration of knowledge, moving beyond surface-level memorization. This study is grounded in Indonesian educational literature and employs a mixed-methods approach involving quasi-experimental design, classroom observation, and interviews. The findings indicate that deep learning significantly improves students’ critical thinking abilities, including analysis, evaluation, and synthesis, as well as historical thinking skills such as understanding historical context, interpreting sources, and constructing reasoned historical explanations. The study concludes that deep learning provides an effective pedagogical framework for history education in Indonesia, particularly in fostering higher-order thinking skills aligned with contemporary curriculum demands.